a) \(A=\dfrac{x^2-3x+4}{x^2-1}=\dfrac{x^2+x-4x-4}{\left(x-1\right)\left(x+1\right)}\)
\(=\dfrac{\left(x^2+x\right)-\left(4x+4\right)}{\left(x-1\right)\left(x+1\right)}\)
\(=\dfrac{x\left(x+1\right)-4\left(x+1\right)}{\left(x-1\right)\left(x+1\right)}\)
\(=\dfrac{\left(x+1\right)\left(x-4\right)}{\left(x-1\right)\left(x+1\right)}\)
\(=\dfrac{x-4}{x-1}\)
b) Ta có:
\(A=\dfrac{x-4}{x-1}=\dfrac{x-1-3}{x-1}=1-\dfrac{3}{x-1}\)
Để A là số nguyên thì \(3⋮\left(x-1\right)\)
\(\Rightarrow x-1\inƯ\left(3\right)=\left\{-3;-1;1;3\right\}\)
\(\Rightarrow x\in\left\{-2;0;2;4\right\}\)
Vậy \(x\in\left\{-2;0;2;4\right\}\) thì A nguyên